Comprehensive circular RNA profiling reveals the regulatory role of the circRNA-100338/miR-141-3p pathway in hepatitis B-related hepatocellular carcinoma - Xiu-Yan Huang (Nature Portfolio, 2017)
Abstract Circular RNAs (circRNAs) represent a class of endogenous noncoding RNAs that have recently been recognized as important regulators of gene expression and pathological networks. However, their transcriptional activities and functional mechanisms in cancer remain largely unknown. Here, we present results from a global circRNA expression and functional analysis of patients with hepatocellular carcinoma (HCC). Using a circRNA microarray, we identified 226 differentially expressed circRNAs, of which 189 were significantly upregulated and 37 were downregulated. High expression of circRNA_100338, one of the upregulated circRNAs in HCC, is closely correlated with a low cumulative survival rate and metastatic progression in HCC patients with hepatitis B. Furthermore, our in silico and experimental analyses identified miR-141-3p as a direct target of circRNA_100338. Thus, circRNA_100338 functions as an endogenous sponge for miR-141-3p in HCC. In addition, we identified the crucial antagonistic roles of circRNA_100338 and miR-141-3p in the regulation of invasive potential in liver cancer cells. Overall, the differential expression of multiple circRNAs in HCC tissues and their clinical significance in hepatitis B-related HCC patients as revealed by our study suggests that circRNA_100338 is a potentially valuable biomarker for HCC diagnosis and target for HCC therapeutics.